The New International Money Game - Aliber, Robert Z. 1930- (Palgrave Macmillan UK, 2002)
When Robert Z. Aliber's The International Money Game first appeared in 1973, it was widely acclaimed as the best - and most entertaining - introduction to the arcane mysteries of international finance on the market. The sixth edition of this classic work has again been fully rewritten to take account of the immense changes in the world economy since the previous edition - financial globalization; post-communist transition; European integration; the Asian crisis and Chinese liberalization. A substantive preface surveys the great changes in the twenty five years since the book first appeared